2019
DOI: 10.3389/fenvs.2019.00188
|View full text |Cite
|
Sign up to set email alerts
|

Citywide Inclusive Sanitation Through Scheduled Desludging Services: Emerging Experience From India

Abstract: The focus of Swachh Bharat Mission (Clean India Mission) was to build toilets to make India open defecation free. While India has succeeded in achieving this goal, to move toward "safely managed sanitation" as per target 6.2 of the Sustainable Development Goals, it is necessary to ensure that all fecal waste is safely collected and treated. The common practice for desludging of septic tanks is "demand-based desludging" rather than a regular service. Such practices have adverse social and environmental impacts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…While one sanitation market assessment [38] found that suppliers knew about the potential public health risks associated with 'uncontained' tanks, they reported that their business is driven by customer preference, indicating the need for effective communication to improve the perception on safe sanitation and raise awareness among the public. While standards for desludging frequencies vary across countries, ranging from 2 to 5 years [41], regular desludging of septic tanks is necessary to ensure functionality of the systems and prevent environmental pollution [8]. Moreover, a recent study estimated that half of on-site sanitation facilities are manually emptied in LMICs [42], pointing to the need for safe emptying practices to achieve safely managed sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…While one sanitation market assessment [38] found that suppliers knew about the potential public health risks associated with 'uncontained' tanks, they reported that their business is driven by customer preference, indicating the need for effective communication to improve the perception on safe sanitation and raise awareness among the public. While standards for desludging frequencies vary across countries, ranging from 2 to 5 years [41], regular desludging of septic tanks is necessary to ensure functionality of the systems and prevent environmental pollution [8]. Moreover, a recent study estimated that half of on-site sanitation facilities are manually emptied in LMICs [42], pointing to the need for safe emptying practices to achieve safely managed sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…Delvic Sanitation Initiatives in Senegal is one such example where an entrepreneur seeks to build profitable and sustainable businesses by providing urban sanitation solutions adapted to the West African market needs (100). Digital innovations would allow for better planning, maintenance, and monitoring of decentralized and/or remote systems, where lack of monitoring often leads to failure (66,75) and such use of digitalization has proven to be cost-effective and successful in sanitation service provision (101).…”
Section: Management and Governancementioning
confidence: 99%
“…It also involves the use of approved mechanical/ motorised equipment (e.g., vacuum trucks) and trained manual emptiers with personal protective equipment (PPE) (e.g., Gulpers) (Parkinson and Quader, 2008;Mondal, 2018;Mondal et al, 2018;Kugedera, 2019). On the other hand, on-demand/emergency emptying is unsafe and occurs only when the system overflows or stops working (ISF-UTS and SNV, 2019;Mehta et al, 2019) or effluents are directly discharged into the environment while unsafe desludging is done manually by unskilled-workers with improvised tools and no personal protective equipment (PPE) could be fatal for the workers (Tyagi, 2017). The authors of this paper conducted a study of 80 households in Khulna Ward 9 (Bangladesh) to determine the prevailing emptying behaviour in the study area and the appropriate behaviour change strategies required.…”
mentioning
confidence: 99%
“…The related health and safety risks of exposure to users and workers make it expedient to address how sanitation containment technologies (e.g., septic tank, aqua privies and pit latrines) are emptied because inappropriate collection and delivery of faecal sludge for proper treatment cause serious public and environmental health consequences (Eales, 2005;Kengne et al, 2011;Peal et al, 2014;Murungi and Pieter van Dijk, 2014;Strande et al, 2018). When desludging is irregular or delayed it affects the effective functioning of the sanitation containment system and then lead to overflow and spill over into the surrounding environment with poor quality effluents (ISF-UTS and SNV, 2019;Mehta et al, 2019). Worse still, these poor quality effluents most often end up in waterbodies, soil and urban spaces, which could negatively impact the health and environment of close communities (Peal et al, 2014;Strande et al, 2014;Appiah-Effah et al, 2014;Mills et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation